Based on Environmental Education: The Effects of Environmental Knowledge and Awareness on the Purchase Intention of New Energy Vehicles in the Southern part of China - Moyo, Ngqabutho; Masuku, Faith (Advances in Social Sciences Research Journal, 2018)
The main objective of this study was to examine the effects of environmental knowledge and awareness on the purchase intention of NEVs, particularly in the southern part of China. In addition to that, this research was also aimed at reflecting the pivotal role played by environmental education in the acquisition of environmental knowledge and awareness. Moreover, this study was also seeking to unearth the influential role of perceived benefits and perceived risks in the purchase decision of NEVs. Stratified random sampling was used as a sampling technique for a targeted sample of participants living in Guangzhou and Shenzhen. This research made use of a qualitative approach to elicit data from the targeted respondents. The outcome of this research shows that environmental knowledge and awareness play a significant role in the purchase intention of NEVs. This research indicates that consumers who are fully equipped with the general knowledge and awareness of their environment are more willing to purchase NEVs, however they also consider other factors such as perceived risks and perceived benefits of NEVs. The goal of environmental education is to impart societal members with the general knowledge and awareness of their environment. This is meant to reinforce sustainable human behaviours and encourage green purchase behaviour. The government of China should therefore continue to improve its environmental education system in order to ensure that it addresses the current issues and adapts to the international standards. In addition, it is also recommended that the perceived risks of NEVs such as; vehicle performance, maintenance costs, possible top speed, driving range, and vehicle safety among others, are addressed in order to enhance the attractiveness of NEVs.